Evaluation of the antioxidant and longevity-promoting effects of white tea extract in Drosophila melanogaster - Yang, Yuhua; Ye, Tingting; Yu, Jingyi; Fan, Li; Ma, Chunhua; Zhang, Bo; Tan, Thuan-Chew (Frontiers in Nutrition, 2025)
IntroductionWhite tea is known for its health benefits, especially its strong antioxidant activity.MethodsBased on previous studies showing white tea extract (WTE) has antioxidant effects in vitro, this research further evaluated its potential to delay aging in Drosophila melanogaster.ResultsThe results showed that dietary supplementation with WTE significantly (p < 0.05) increased both the mean lifespan (Tm) and longest survival time (Tmax) of Drosophila melanogaster. Tm levels rose by 15.41% in males and 30.39% in females at 3 mg/mL concentration, while the Tmax showed increases of 21.05 and 32.27%, respectively. WTE also improved the flies’ climbing ability and their resistance to hydrogen peroxide-induced stress. It markedly (p < 0.05) decreased malondialdehyde (MDA) concentrations while enhancing the activities of antioxidant enzymes, such as total superoxide dismutase (T-SOD) and catalase (CAT), in a dose-responsive manner. Gene expression analysis indicated that WTE significantly upregulated the antioxidant-related genes SOD1, SOD2, and CAT, while suppressing the expression of the aging-related MTH gene.DiscussionOverall, WTE helps delay aging in fruit flies by boosting antioxidant defenses and reducing oxidative damage. These results suggest its potential use as a natural antioxidant and anti-aging ingredient in food and health products.